Colossal thermo-hydro-electrochemical voltage generation for self-sustainable operation of electronics - Yufan Zhang (Nature Portfolio, 2021)
Thermoelectrics are suited to converting dissipated heat into electricity for operating electronics but limited by the small voltage from the Seebeck effect. Here, the authors report a thermo-hydro-electrochemical hybrid device with −87 mV K−1.